Effect of Package Type and Storage Temperature on Quality of Probiotic Fortified Vegetable Tablets - Thongmat, Krongkan; Assatarakul, Kitipong (Journal of Food Technology, Siam University, 2019)
The objectives of this study were to investigate the effect of packaging type (aluminum foil bag and high density polyethylene or HDPE plastic bottle) and storage temperature (4 ํC and 25 ํC) on quality of probiotic fortified vegetable tablets by monitoring the change of the color values, total phenolic content (TPC), antioxidant activity by 2, 2-diphenyl-1-picrylhydrazyl radical scavenging activity (DPPH) assay and the survival of probiotics (Lactobacillus rhamnosus) during the storage. Samples were evaluated for each parameters every week for 4 weeks. The results showed that the storage of probiotic fortified vegetable tablets at 4 ํC and 25 ํC in two types of packaging including aluminum foil bag and HDPE plastic bottle did not affect product color changes. An increase in storage time resulted in a lower in total phenolic content and antioxidant activity. Total phenolic content and antioxidant activity of samples stored at 4 ํC were higher than samples stored at 25 ํC. Similarly, the number of viable cells of probiotics strains L. rhamnosus in all storage conditions tended to decrease when the storage time increased. The survival of L. rhamnosus of samples stored at 4 ํC was higher than samples stored at 25 ํC. In addition, the number of viable L. rhamnosus of the sample stored at 4 ํC was still approximately 6 log CFU/g according to food product standards from probiotics in the Ministry of Public Health announcement at the end of the storage for 4 weeks and the packaging type did not affect the survival of probiotics during the storage.